DIMENSI UTAMA DAN STABILITAS KAPAL PANCING TONDA DI WANGI-WANGI KABUPATEN WAKATOBI - Kumala Sari Ode Murhum; Yopi Novita; Mohammad Imron; Didin Komarudin (Fakultas Perikanan dan Ilmu Kelautan, 2022)
Based on ship accident report data, during 2016-2020 there were 65 cases of ship accidents reported. The occurrence of a capsized ship is caused by poor ship stability or the main dimensions of the ship that are not in accordance with its designation. This study aims to identify the main dimensions and analyze the stability of the troll liner used by fishermen in Wangi-Wangi. The data collection technique used was accidental sampling. The results showed that the troll liner at Wangi-Wangi had the main dimension ratio values of L/B mostly (90,37%) in accordance with the reference values, the overall B/D ratio values (100%) were in accordance with the range of reference values, and the value of the L/D ratio is only a small portion (21,39%) within the reference range. The troll liner at Wangi-Wangi have a positive stability arm (GZ) value so that they have the ability to return to their original (stable) position after experiencing a tilt. The GZ value of the ship is directly proportional to the size and condition of the ship's cargo, where the greater the size and condition of the ship's cargo, the greater the GZ value of the ship.